Cross-interpreting in Slovakia: a tabooed reality - Dorčák, Štefan (Ukrainian linguistics, 2021)
The present paper is a partial research work within the author’s dissertation thesis and seeks evidence to refute or support the hypothesis that interpreters are more effective in terms of quality when working into their mother tongue in comparison with interpreters working between two foreign languages. The data for this study were collected via interpreting questionnaires with thirteen selected criteria (e.g. native accent, pleasant voice, exaggerated fillers, fluency of delivery, logical cohesion, sense consistency, completeness of interpretation, significant omissions, use of correct terminology, etc.) that had been filled out (assessed on a 5-grade scale) by three target groups (professional interpreters, students of interpreting and so-called delegates), after having listened to three records of simultaneous interpretation (from English into Russian/Ukrainian). The records include three conference interpretations of a speech by NATO Secretary-General, Jens Stoltenberg, delivered in English on defensce and political topics. Two of the three interpreters (N 1 and N 2) are native speakers of the target language, while the third interpreter (N 3) works between two foreign languages. This paper presents the results for three target groups’ rating of the selected quality criteria for simultaneous interpretation. The aim of the present paper lies within comparing the output-related quality of B to A language interpreting vs. B to B language interpreting from the audience quality perception point of view. Information about the author:Štefan Dorčák – PhD, Univerzita Mateja Bela v Banskej Bystrici (Slovakia).E-mail: sdorcak@umb.sk__________References• AIIC (1982). Practical Guide for Professional Interpreters, Geneva, AIIC. URL : https://aiic.org/site/world/about/profession/abc(in English).• Bohušová Z. (2017) Sprachlich und kommunikativ bedingte Neutralisierungen beim Dolmetschen [Language and communication conditioned neutralizations in interpretation]. Wien: Praesens Verlag, 170 р. (in German).• Bohušová Z. (2008). Subjektívne vnímanie tlmočníckeho výkonu poslucháčmi a problematika posudzovania kvality translačnej služby [Subjective perception of interpreting by listeners and the interpreting quality output evaluation issues]. Praha: Jednota tlumočníků a překladatelů, рр. 17–26 (in Slovak).• Bühler H. (1986). Linguistic (semantic) and extra-linguistic (pragmatic) criteria for the evaluation of conference interpretation and interpreters. Multilingua, 5:4, рр. 231–235 (in English).• De Fortis C.G. (2007). Some thoughts of “B” language, Interpreter Training Resources. URL : https://interpretertrainingresources.eu/language /a-few-thoughts-on-b-languages/(in English).• Déjean Le Féal K. (1990). Some Thoughts on the Evaluation of Simultaneous Interpretation, Interpreting – Yesterday, Today, and Tomorrow. Binghamton(NY), SUNY, pp. 154–160 (in English).• Denissenko J. (1989). The theoretical and practical aspects of teaching conference interpretation. Communicative and Interpretive Linguistics, pp. 155–157 (in English).• Gile D. (1990). L’évaluation de la qualité du travail par les délégués: une étude de cas [Evaluation of quality by delegates]. The Interpreters’ Newsletter, no 3, рp. 66–71 (in French).• Herbert J. (1978). How Conference Interpretation Grew. Language Interpretation and Communication. New York–London: Plenum Press, pp. 5–10 (in English).• Kahane E. (2000). Thoughts on the Quality of Interpretation, Communicate! Issue 4, May 2000, on AIIC homepage (AIIC Online). URL : http://www.aiic.net/ViewPage.cfm/page197.htm> (in English).• Keníž A. (1980). Úvod do komunikačnej teórie tlmočenia [Introduction to the interpreting communication theory]. Bratislava: Univerzita Komenského (in Slovak).• Kurz I. (2001). Conference Interpreting: Quality in the Ears of the User. Meta, 46 (2), 394–409. URL : https://doi.org/10.7202/003364ar(in English).• Kurz I. (1989). Conference interpreting user expectations, Coming of age. proceedings of the 30th conference of the a.t.a., Medford, N:J: Learned Information Inc., рр. 143–148 (in English).• Lambert W. (1978). Psychological Approaches to Bilingualism, Translation and Interpretation. Language Interpretation and Communication. New York – London: Plenum Press, pp. 131–142 (in English).• Machová L. (2016). Hodnotiaci formulár ako nástroj tlmočníckej sebareflexie u študentov: Didaktické východisko. Dizertačná práca [Evaluation form as a tool for students’ self-reflection at interpreting: Didactical approach. Dissertation thesis]. Bratislava, 167 р (in Slovak).• Moser-Merceret. al. (1998). Prolonged turns in interpreting: effects on quality, physiological and psychological stress. Interpreting, vol. 3, Issue 1, Jan 1998, pр. 47–64 (in English).• Qian H. (1994). Looking at Interpretation from a Communicative Perspective. Babel, 40(4), pp. 214–221 (in English).• Qzar M.H. (1997). The Role of Memory as a Cognitive Psychological Faculty in Simultaneous Interpretation. Unpublished M.A. Thesis, Yarmouk University, Jordan (in English).• Schweda-Nicholson N. (1992). Linguistic theory and simultaneous interpretation: Semantic and pragmatic considerations. Babel, 38(2), рр. 90–100 (in English).• Seleskovitch D. and Lederer M. (1986). Who Should Assess an Interpreter’s Performance? Multilingua, 5:4, p. 236 (in English).• Stahl J. (2012). Kvalita tlmočenia v teórii a praxi [Quality of interpreting in theory and practice]. Kontexty súdneho prekladu a tlmočenia. Bratislava: Univerzita Komenského, 2012, рр. 112–121 (in Slovak).• Šveda P. (2016). Vybrané kapitoly z didaktiky simultánneho tlmočenia [Selected chapters from the didactics of simultaneous interpreting]. Bratislava: Univerzita Komenského v Bratislave, 2016, 95 р. (in Slovak).• Zwischenberger C. (2010). Quality criteria in simultaneous interpreting: an international vs. a national view. The Interpreters’ Newsletter, 15 (in Slovak).
Keywords: conference interpreting, cross-interpreting, interpreting quality assessment, interpreting political discourse, B to B language interpreting